Conditions for the effectiveness of studying physics and mathematics in the formation of professional competence in technical university students - Kanashevich, Tatiana N. (University Pedagogical Journal, 2021)
The article deals with the problem of improving the quality of training of specialists with higher technical education by focusing on the formation of professional competence. Organisational and methodological conditions stimulating students’ learning activities efficiency in studying physical and mathematical disciplines that provide important information-intellectual and practical-empirical basis for successful mastering by future specialists of general technical and specialisation disciplines, mastering professional competence are suggested and justified. An analysis of the results of the long-term research work with the assessment of their statistical significance is presented.
Keywords: student learning activities; effectiveness; conditions; professional competence